Adjuvant Bidirectional Chemotherapy with Intraperitoneal Pemetrexed Combined with Intravenous Cisplatin for Diffuse Malignant Peritoneal Mesothelioma - Bijelic, Lana (Hindawi Publishing Corporation, 2012)
Cytoreductive surgery (CRS) with heated intraoperative intraperitoneal chemotherapy (HIPEC) has emerged as optimal treatment for diffuse malignant peritoneal mesothelioma (DMPM) showing median survivals of 36–92 months. However, recurrences occur frequently even in patients undergoing optimal cytreduction and are often confined to the abdomen. We initiated a Phase II study of adjuvant intraperitoneal pemetrexed combined with intravenous cisplatin for patients undergoing CRS and HIPEC for DMPM. The treatment consisted of pemetrexed 500 mg/m(2) intraperitoneally and cisplatin 50 mg/m(2) intravenously given simultaneously on day 1 of every 21 day cycle for 6 cycles. The primary endpoint of the study was treatment related toxicity. From July 2007 until July 2009 ten patients were enrolled. Nine of 10 completed all 6 cycles of adjuvant treatment per protocol. The most common toxicities were fatigue, nausea and abdominal pain grade 1 or 2. There was one grade 3 toxicity consisting of a catheter infection. The median survival for all 10 patients was 33.5 months. Pharmacokinetic analysis of intraperitoneal pemetrexed showed a peritoneal to plasma area under the curve ratio of 70. Our study shows that adjuvant intravenous cisplatin and intraperitoneal pemetrexed can be used following CRS and HIPEC for DMPM with low morbidity.